Is the country-level income an important factor to consider for COVID-19 control? An analysis of selected 100 countries - (:unkn) unknown (EMERALD GROUP PUBLISHING LTD, 2021)
Purpose The purpose of this study is to evaluate the association between economic activity in a country, as measured by the gross domestic product (GDP) and the control of the COVID-19 pandemic outcomes, as measured by the rate of incidence and mortality increase per 100,000 population in different countries using up-to-date data, in the light of public health security capacities including prevention, detection, respond, enabling function, operational readiness, as measured by the 2019 State Party self-assessment annual reporting (SPAR) submissions of 100 countries. Design/methodology/approach For this analytical study, multiple linear regression analyses were performed for each variable with the COVID-19 incidence and mortality rates, while controlling for Human Development Index (HDI) and GDP. Findings Countries with higher income levels were significantly more likely to have a higher incidence and mortality rate per 100,000 population. Among the public health capacity categories, prevention of the infectious disease and detection of the pathogens were significantly associated with lower incidence and mortality of the COVID-19 pandemic. The country-level income was found to be an important negative predictor of COVID-19 control. Practical implications These findings present to decision-makers in organizing mitigation strategies to struggle emerging infectious pandemics and highlight the role of country-level income while trying to control COVID-19. In order to determine the priority settings for the fight against pandemic, national policy-makers and international organizations should notice that countries in a high-income group had better health security capacities than that of other income groups, particularly in low- and lower-middle-income groups. The results of the capabilities of health security by the income group can assist health policy makers and other international agencies in resource allocation decisions and in mitigating risk with more informed resource planning. Social implications The income level of countries may have a positive effect on public health strategies to mitigate the risk of infection of COVID-19. This study may assist the local public authorities to gain a better level of understanding on the relationship country-level income and COVID-19 outcomes in order to take appropriate measures at the local level. The results also highlighted the importance role of public health security capacities for the pandemic control policy. Originality/value Although previous studies have examined to assess the public health capability by country-level and to describe cases and deaths by continent and by country, very limited studies have evaluated the rate of incidence and mortality of COVID-19 by country-level income and by health expenditure using the data on the health security capacities with analytical and practical approaches.
Keywords: COVID-19; Public health security; Incidence; Mortality; Countries